Using Cooking Schools to Improve the Pleasure of Food and Cooking in Patients Experiencing Smell Loss - Fjaeldstad, AW (MDPI, 2024)
Smell loss affects around 15–20% of the population, with a major effect on the quality of life. The most common complaint is the impairment of the eating experience, with around 90% of patients reporting this issue. A study conducted at a specialised Taste and Smell Clinic investigated if food and cooking can positively affect the enjoyment of food, subjective cooking skills, and quality of life in patients with smell loss. The 49 participants in the study received a 5-week cooking school course that focused on emphasizing the other senses to regain the enjoyment of food. Participants gained more confidence in cooking, and their quality of life improved significantly. Positively evaluated recipes were adjusted based on feedback and published as free e-books in Danish, German, and English. Eating and cooking are multisensory experiences, and the perception of food depends on the complex interaction of senses and surroundings. If the olfactory input is reduced or absent, both the enjoyment and cooking experience can be negatively affected. Therefore, focusing on food and cooking can have a positive impact on patients with smell loss.